2019
DOI: 10.1016/j.celrep.2019.03.080
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA Spehd Regulates Hematopoietic Stem and Progenitor Cells and Is Required for Multilineage Differentiation

Abstract: Summary Long non-coding RNAs (lncRNAs) show patterns of tissue- and cell type-specific expression that are very similar to those of protein coding genes and consequently have the potential to control stem and progenitor cell fate decisions along a differentiation trajectory. To understand the roles that lncRNAs may play in hematopoiesis, we selected a subset of mouse lncRNAs with potentially relevant expression patterns and refined our candidate list using evidence of conserved expression in human b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…A summary-data-based Mendelian randomization analysis that uses rs3809674 as an instrumental variable, predicts an effect of CEROX1 gene expression on glioma risk (Melin et al, 2017). Finally, it has recently been demonstrated in a mouse model of haematopoietic lineage differentiation that Cerox1 depletion may impair the contributions of stem cell or B cell differentiation to haematopoiesis (Delás et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A summary-data-based Mendelian randomization analysis that uses rs3809674 as an instrumental variable, predicts an effect of CEROX1 gene expression on glioma risk (Melin et al, 2017). Finally, it has recently been demonstrated in a mouse model of haematopoietic lineage differentiation that Cerox1 depletion may impair the contributions of stem cell or B cell differentiation to haematopoiesis (Delás et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a type of RNA of >200 nucleotides in length that do not encode for proteins. Following their discovery, lncRNAs were considered as ‘noises’ in the genome transcription process ( 19 , 20 ). However, subsequent studies demonstrated that lncRNAs regulate genes at a number of levels, including epigenetic, genomic transcription and post-transcriptional levels.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that lncRNAs were involved in various cellular functions, including cell proliferation, cell growth, cell differentiation and apoptosis. [8][9][10] The abnormal expression of lncRNAs was revealed in many diseases, including cancer, pulmonary fibrosis, and COPD. [11][12][13][14][15] Recently, increasing evidence has shown that HOXA cluster antisense RNA 2 (HOXA-AS2), a lncRNA located between and antisense to the human HOXA3 and HOXA4 genes, is associated with cell survival, proliferation and invasion.…”
Section: Introductionmentioning
confidence: 99%